INTERCESSION IN THE QUR'AN CRITICAL ANALYSIS INTERPRETATION OF AL-MARAGHI - Kazuba, Mahfudz; M., M. Ghalib; Abubakar, Achmad; Firdaus (Jurnal Diskursus Islam, 2022)
Man will not be separated from intercession because in human life, even until death, he still needs intercession. People who genuinely have faith in Allah swt. Submit and obey the sharia to Him. Islam sets the standard of morality based on the provisions of Allah and His Messenger. Therefore, what is seen as good by Allah and His Messenger, must be good. Moreover, vice versa, it cannot be Allah swt. He was judging falsehood as good behavior because the falsehood of its essence must be immoral. Thus in every explanation relating to intercession," at be it those who give and get intercession" at, or whether those who are hindered from it are clear that the cause is the scientific dimension related to faith in Allah swt. and sharia according to the provisions of Allah swt. and akhlakul karimah in doing the good of others.